Novel activated carbon nanofibers composited with cost-effective graphene-based materials for enhanced adsorption performance toward methane - Othman, F.E.C. (MDPI AG, 2020)
Various types of activated carbon nanofibers' (ACNFs) composites have been extensively studied and reported recently due to their extraordinary properties and applications. This study reports the fabrication and assessments of ACNFs incorporated with graphene-based materials, known as gACNFs, via simple electrospinning and subsequent physical activation process. TGA analysis proved graphene-derived rice husk ashes (GRHA)/ACNFs possess twice the carbon yield and thermally stable properties compared to other samples. Raman spectra, XRD, and FTIR analyses explained the chemical structures in all resultant gACNFs samples. The SEM and EDX results revealed the average fiber diameters of the gACNFs, ranging from 250 to 400 nm, and the successful incorporation of both GRHA and reduced graphene oxide (rGO) into the ACNFs' structures. The results revealed that ACNFs incorporated with GRHA possesses the highest specific surface area (SSA), of 384 m2/g, with high micropore volume, of 0.1580 cm3/g, which is up to 88 of the total pore volume. The GRHA/ACNF was found to be a better adsorbent for CH4 compared to pristine ACNFs and reduced graphene oxide (rGO/ACNF) as it showed sorption up to 66.40 mmol/g at 25 Â°C and 12 bar. The sorption capacity of the GRHA/ACNF was impressively higher than earlier reported studies on ACNFs and ACNF composites. Interestingly, the CH4 adsorption of all ACNF samples obeyed the pseudo-second-order kinetic model at low pressure (4 bar), indicating the chemisorption behaviors. However, it obeyed the pseudo-first order at higher pressures (8 and 12 bar), indicating the physisorption behaviors. These results correspond to the textural properties that describe that the high adsorption capacity of CH4 at high pressure is mainly dependent upon the specific surface area (SSA), pore size distribution, and the suitable range of pore size. Â© 2020 by the authors.